A Literary And Socio-Cultural Analysis Of Polygynous Practices Among The Yorùbá Deities - Saadu, Taofiq; Ojo, Ilufoye Fawole; Ajewole, Fola (Journal of Gender and Power, 2025)
This study examines the conflicting perspectives on polygyny within Yoruba culture, focusing on two Ifá oral genres: Ọ̀yẹ̀kú Méjì and Ọ̀sẹ́ Bàrà, one of which critiques polygyny as a source of societal discord while the other endorses it. It argues that both the advantages and disadvantages of polygyny in African society are culturally rooted in African cosmology, particularly Yoruba mythology. The study also observes that existing scholarly works on polygyny primarily focus on its contribution to marital instability and family breakdown, while neglecting its perceived benefits. This research therefore addresses an existing gap in the literature by analyzing both the socio-cultural benefits and implications of polygyny through Ifá orature, exploring its influence on contemporary marital dynamics and unintended outcomes such as polyandry. The study adopts a mixed-methods approach, using primary data from in-depth interviews with purposively selected Ifá priests and priestesses in Southwestern Nigeria. The interviews were recorded to ensure accuracy. Secondary sources include books, journal articles, and credible internet resources. The data were transcribed, translated, and analyzed within a socio-cultural theoretical framework to assess the impact of polygyny on gender relations and social structures. The findings reveal that Ọ̀yẹ̀kú Méjì's critique aligns with concerns about marital discord, whereas Ọ̀sẹ́ Bàrà's endorsement reinforces the practice of polygyny among kings and farmers. However, it also marginalizes women, fostering resentment and contributing to family breakdown. The study underscores the need to re-evaluate polygyny in order to promote more equitable relationships. By bridging traditional Ifá orature and contemporary practices, this research offers a nuanced understanding of the socio-cultural effects of polygyny, advocates for greater alignment with modern egalitarian values, and contributes to broader discussions of African cultural heritage.